TRANSFORMATION OF RELIGIOUS EDUCATION IN INDONESIA: A CRITICAL EVALUATION OF GOVERNMENT POLICY IMPLEMENTATION - Mukhtar Mas’ud (Program Pascasarjana UIN Sumatera Utara, 2025)
This study aims to critically evaluate the substance, evolution, and implementation of government policies on religious education transformation in Indonesia. It analyzes how policies have shifted from normative approaches toward integrative, competency-based models aligned with Indonesia Emas 2045. The research employs a qualitative descriptive method with a critical evaluation approach through literature study (library research). Data were collected from secondary sources including official policy documents (UU No. 20/2003, PP No. 55/2007, Kurikulum Merdeka, Peta Jalan Pendidikan Islam 2023-2045, and Asta Protas), government reports, and related studies, analyzed using content analysis and policy implementation frameworks (top-down vs bottom-up). The results reveal significant policy evolution toward integration of science-religion, digitalization, and eco-theology. However, field implementation remains suboptimal with low effectiveness due to teachers’ difficulties in implementing differentiated project-based learning, inefficient budget allocation especially in private madrasahs, and serious equity gaps between urban public and rural/remote institutions. Supporting factors such as government commitment and inter-ministerial cooperation are overshadowed by structural (human resources, infrastructure, funding) and cultural (traditional pesantren resistance) barriers. In conclusion, although the policy framework is progressive, the transformation is hampered by top-down implementation that lacks local participation. Holistic recommendations include massive teacher training, targeted funding for disadvantaged areas, bottom-up participatory models, and integrated digital monitoring systems. This study contributes to bridging the gap between macro policy and micro reality in religious education